Proteolysis in Danish blue cheese during ripening. (October 2019) - Mane, A.; Ciocia, F.; Beck, T.K.; Lillevang, S.K.; McSweeney, P.L.H.
Abstract: Proteolysis in Danish blue cheese was studied during 9 weeks' ripening. Levels of pH 4.6-soluble N as a percentage of total N increased from 7.2% to 25%, indicating extensive proteolysis. Urea-polyacrylamide gel electrophoretograms confirmed the extent of proteolysis through chymosin and plasmin action early in ripening, but later the action of Penicillium roqueforti proteinases became apparent. The proteolytic specificity of Penicillium roqueforti PR-R proteinases on αS1 - and β-casein was determined in a model system. Regions most susceptible to proteinase action in αS1 -casein were 6–40, 69–99, 124–147 and 155–199, with a total of 91 cleavage sites identified; regions in β-casein susceptible to proteolysis were 43–87, 101–119, 161–185 and 192–209 with a total of 118 cleavage sites identified. A large number of peptides was identified cheese extracts during 9 weeks ripening, principally from αS1 -casein regions 1–40, 105–136 and 150–176 and β-casein regions 6–14, 46–68, 101–140 and 193–209.